Meningkatan Keaktifan Belajar Siswa pada Mata Pelajaran IPA melalui Model Tiruan Berbasis Teknologi Informasi di SD 158/III Sungai Abu - Pandya, Pebri Azmi; Sidik, Muhammad; Hayati, Suci; Diva, Fadelina Wizola; Fazliani, Bella; Amini, Anisa (MASALIQ, 2023)
This study aims to increase students' active learning in science subjects by using an artificial model based on Information Technology. This type of research is classroom action research (CAR). This research was conducted in class V with a total of 6 male students and 5 female students. This research consisted of two cycles and each cycle held two meetings. Data collection techniques using observation techniques, and documentation. The results showed that there was an increase in student learning activeness in science subjects by using a mock model from cycle I to cycle II. The increase in student activity occurred because students had understood the concept of learning science through the steps contained in the Information technology-based artificial learning model, and students were more enthusiastic in participating in the learning process. The percentage of student activity in cycle II increased from 73.8% to 82.9% classically.